2020
DOI: 10.3991/ijim.v14i02.11658
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mobile Technologies for the Formation of Analytical Competence of Future Specialists

Abstract: The article deals with application of mobile technologies for the formation of analytical competence of future specialists. It discusses the concepts of mobile learning and mobile technologies. Advantages of using mobile technologies within the learning process are presented. The use of mobile learning is one of the most effective and affordable ways of formation of students' analytical competence. Managing, strategic, informational, reflexive components within the structure of analytical competence are reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Socio-economic and technical changes along with the information society and digital economy needs have determined the trends towards the introduction of software, computer and information technologies, reduction of printed papers, digitization of almost all spheres of the socio-economic life. This requires that the educational content should be updated in the new conditions of digital technological opportunities [28]. The exponential growth of technology has determined the primary goal of higher education institutions, which is to improve learning outcomes and academic performance by integrating students with mobile learning [13].…”
Section: Resultsmentioning
confidence: 99%
“…Socio-economic and technical changes along with the information society and digital economy needs have determined the trends towards the introduction of software, computer and information technologies, reduction of printed papers, digitization of almost all spheres of the socio-economic life. This requires that the educational content should be updated in the new conditions of digital technological opportunities [28]. The exponential growth of technology has determined the primary goal of higher education institutions, which is to improve learning outcomes and academic performance by integrating students with mobile learning [13].…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the use of mobile learning strongly supports these activities which are carried out directly and in real-time [24]. Mobile learning allows students to gather knowledge from various sources and enabling the production of more meaningful learning [30]. In addition, since students are known to be the digital native generation, this type of learning should be developed from the age of basic education [31].…”
Section: Discussionmentioning
confidence: 99%
“…The use of smart applications in various purposes is a current trend, the ease and effectiveness of this application is the main purpose of its use. Research on the use of smart applications can be found in various purposes such as youth financial management [31], science learning in primary school [32], disseminating messages and events of university colleges [33], and the formation of analytical competence of future specialists [34], including in the field of sports education [35]. The use of smart applications in sports education, such as the smart application in swimming, is interesting to discuss, because the use of smart applications in learning to swim is something that can give students interest and interest in learning to swim.…”
Section: Multicollinearity Testmentioning
confidence: 99%